Predictors of intention to integrate biofortified orange-fleshed sweetpotato in child feeding: A field information experiment in rural Kenya - Lagerkvist, Carl Johan; Mutiso, J.M.; Okello, J.J.; Muoki, Penina Ngusye; Oluoch-Kosura, Willis; Heck, S. (Informa UK Limited, 2020)
The study assesses the psychosocial predictors of intention to integrate biofortified pro-vitamin A orange-fleshed sweet potato (OFSP) in proper complementary feeding (PCF) among women who received either verbal or verbal and visual demonstrations on OFSP-based foods. A total of 764 randomly selected women grouped into four categories, namely pregnant women, women with infants, women with young children, and potential mothers, participated in this study. Using a structural equation model of predicted intentions based on an extended Theory of Planned Behavior (TPB) the study found goal-setting, perceived behavior control, subjective norms, and attitudes had a significant influence on intention to integrate OFSP in PCF. Unexpectedly, knowledge of the various health benefits of OFSP did not positively influence intention. Probabilistic recursive regression was then used to estimate the relationship between the intention to provide PCF practices and its potential antecedents. The results then showed that the model structure and explanatory power was information-specific and also revealing outcome differences by category of women. These results have implications on how interventions targeting the improvement of PCF should be organized and delivered. They underscore the need to segment the audience during nutrition education.